(3JeMjU GdJdNjUs - (3MSf Hf WhQNGf Hf OGhO Hf jYbhH GdCbMUGQj, hjbGd dg (B((3MSf cGaj(B) (3hGTJgQ HcGaj,J (B1025 (3g` s ((3eMeO Hf MSf GdcQjOi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi CfYe Ydi GdEfSGf , HYde GdeYGfi hGdHjGf , Hjf SGFQ GdCfGe , hGdUdGI Ydi MHjHI GdPi CcQeg HGdbQBf s
(3BNQgG (B:s
(3hgPG BNQ GdJeMjU hddg GdMeO hEdjg GdeMjU Ci GdgQH ef GdMjU hgh GdYOhd Ydi LgI GdaQGQ eUOQ cGdeZjK hbO jchf ecGfkG cGdeHjJ Je HYhf Gddg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3HChdgG agQSJ ddcJGHs
(3HChdg hbajI HGSe YdGeI HjQhJ GdTjN eMeO SYjO Hf eMeO Hc EjGS GdOeTbi CUdkG hGdHjQhJi ehdOkG s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
Keywords: (3GdHdGZIs